The Berenstain Bears and the missing dinosaur bone - Berenstain, Stan, 1923-2005; Berenstain, Jan, 1923-2012 (Beginner Books, 1980)
The three Bear Detectives search for a dinosaur bone that is missing from the Bear Museum.